Clinical Evaluation of a Combination of Dynamic Intramedullary and Cross Pins Construct to Stabilize Supracondylar Femoral Fracture in Dogs - Nikita Gupta; Ashwani Kumar; Vandana Sangwan (The Indian Veterinary Journal, 2024)
The study included four clinical cases of dogs presented with supracondylar femoral fractures that were stabilized with a combination of two stainless steel cross pins and two dynamic intramedullary pins inserted in the normograde fashion from the either sides of condyles. Immediate postoperative radiographs showed excellent (n=3) to fair (n=1)fracture reduction. Subsequent follow ups revealed satisfactory limb usage and functional outcome without any complications. This combination technique provided stable implant construct and combined the advantages of both the above mentioned techniques leading to satisfactory functional outcome. Therefore, combining cross with dynamic intramedullary pinning techniques may have potential to be adopted as an alternative technique for the fixation of supracondylar femoral fractures, particularly, in medium to heavy breed dogs.